Tantangan Akidah Islam dalam Masyarakat Multikultural: Isu Pluralisme, Sinkretisme, dan Relativisme Kebenaran - Nafi Lutfi 'Ulia Ristiana; Febri Amin Nurrohman; Mahmud Arif (Indonesian Journal of Islamic Theology and Philosophy, 2026)
Abstract; This article examines the challenges of the Islamic faith in the context of multicultural societies in the modern era by highlighting three main issues, namely theological pluralism, cultural syncretism, and relativism of truth. The development of an increasingly open society, supported by advances in digital technology, has accelerated interfaith and cultural interactions, while presenting complex theological problems for Muslims. Through a qualitative approach based on literature studies, this article analyzes various theoretical studies and cutting-edge research that addresses these dynamics. The results of the study show that the challenge of faith is not solely born from social diversity, but from the weakening of theological literacy and the shift of religious authority in the digital public space. This article argues that strengthening the Islamic faith in a multicultural society requires epistemological clarity, contextual da'wah, and the active involvement of scholars and academics in building authoritative and inclusive religious understanding. Keywords: Islamic creed; Multiculturalism; Syncretism; Theological pluralism; Truth relativism.   Abstrak; Artikel ini mengkaji tantangan akidah Islam dalam konteks masyarakat multikultural pada era modern dengan menyoroti tiga isu utama, yaitu pluralisme teologis, sinkretisme budaya, dan relativisme kebenaran. Perkembangan masyarakat yang semakin terbuka, ditopang oleh kemajuan teknologi digital, telah mempercepat interaksi lintas agama dan budaya, sekaligus menghadirkan problem teologis yang kompleks bagi umat Islam. Melalui pendekatan kualitatif berbasis studi literatur, artikel ini menganalisis berbagai kajian teoretis dan penelitian mutakhir yang membahas dinamika tersebut. Hasil kajian menunjukkan bahwa tantangan akidah tidak semata-mata lahir dari keberagaman sosial, melainkan dari melemahnya literasi teologis dan pergeseran otoritas keagamaan di ruang publik digital. Artikel ini berargumen bahwa penguatan akidah Islam di masyarakat multikultural menuntut kejelasan epistemologis, dakwah kontekstual, serta keterlibatan aktif ulama dan akademisi dalam membangun pemahaman keagamaan yang otoritatif dan inklusif. Kata Kunci: Akidah Islam; Multikulturalisme; Pluralisme teologis; Relativisme kebenaran; Sinkretisme.